Danske benediktinemonner og deres klostre i det 13.-15. århundrede - Langkilde, Birgitte (Kirkehistoriske Samlinger, 1993)
The Danish medieval nunneries (30 in all, 16 being Benedictine houses) have been somewhat stepmotherly treated in the literature. To remedy this, the author has made a study og the Danish Benedictine nunneries over the period from 1241 to 1536. The results were presented in the form of a thesis for the Master’s degree combined with a lecture. The article, which constitutes a revised edition of the lecture, presents and discusses samples of Benedictine nuns from the 13th, 14th, and 15th centuries respectively, and demonstrates a trend in recruitment: from aristocratic widows in the earlier phase to young gentlewomen in the later - commoners being however also in evidence. Another trend is shown concerning endowments in connection with entry: from very large ‘dowries’ to smaller ones.